Preeclampsia prediction and diagnosis: a comprehensive historical review from clinical insights to omics perspectives - Riano-Moreno, Julian C.; Vargas-Castellanos, Elizabeth; Pedraza, Amy; Díaz-Quiñonez, Laura Sofía; Rangel-Ramos, Víctor Saul (Frontiers in Medicine, 2025)
Preeclampsia (PE) is a multifactorial and multisystemic syndrome specific to human pregnancy, traditionally characterized by hypertension and proteinuria. Affecting 2%−10% of pregnancies, PE remains a leading cause of maternal and perinatal morbidity and mortality, particularly in low- and middle-income countries. This review traces the historical evolution of PE diagnosis, from early clinical observations to the incorporation of modern omics biomarkers. Early diagnostic criteria were based on observable clinical symptoms, but advancements in biomedical science have highlighted the significance of angiogenic and anti-angiogenic factors, such as sFlt-1 and PlGF, which are used as “Established Angiogenic Biomarkers.” Despite these advancements, clinical consensus on the use of these biomarkers remains elusive due to their variable sensitivity. Recent integrative approaches using omics technologies have provided deeper insights into the complex pathophysiology of PE, uncovering new pathways and “Potential Molecular Biomarkers” for early diagnosis and prediction. However, challenges remain in translating these findings into clinical practice, particularly due to the need for robust validation studies and the consideration of inter-individual and population variability. This review emphasizes the importance of continued research and validation of these biomarkers in diverse cohorts to develop effective predictive tools and improve maternal and fetal outcomes. By exploring the historical and modern perspectives on PE diagnosis, this review aims to provide a comprehensive understanding of the disease and highlight future directions in PE research.